2011
DOI: 10.1074/jbc.m111.239210
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Specificity of Pentachloropseudilin-mediated Inhibition of Myosin Motor Activity

Abstract: Here, we report that the natural compound pentachloropseudilin (PClP) acts as a reversible and allosteric inhibitor of myosin ATPase and motor activity. IC50 values are in the range from 1 to 5 μm for mammalian class-1 myosins and greater than 90 μm for class-2 and class-5 myosins, and no inhibition was observed with class-6 and class-7 myosins. We show that in mammalian cells, PClP selectively inhibits myosin-1c function. To elucidate the structural basis for PClP-induced allosteric coupling and isoform-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
81
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 26 publications
3
81
0
4
Order By: Relevance
“…It is important to note that although the potent inhibition of myosin I proteins by PCIP has been characterized in greatest detail, the drug also inhibits the ATPase activity of myosin Vb and nonmuscle myosin II at higher concentrations (IC 50 >90 μM) [54]. This lack of specificity at higher concentrations must be taken into account when designing in vivo experiments using PCIP.…”
Section: Small-molecule Inhibitors Of Myosinsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note that although the potent inhibition of myosin I proteins by PCIP has been characterized in greatest detail, the drug also inhibits the ATPase activity of myosin Vb and nonmuscle myosin II at higher concentrations (IC 50 >90 μM) [54]. This lack of specificity at higher concentrations must be taken into account when designing in vivo experiments using PCIP.…”
Section: Small-molecule Inhibitors Of Myosinsmentioning
confidence: 99%
“…Structural studies of the binding of PCIP to a model myosin (Dictyostelium discoideum myosin II) indicate that the compound binds to an allosteric pocket in the myosin motor domain and thus acts as a noncompetitive inhibitor of motor activity [54]. The PCIP-binding pocket is located near actin-binding residues at the tip of the 50-kDa cleft in the myosin motor domain, approximately 16 Å from the nucleotide binding site and 7.5 Å from the hydrophobic pocket bound by blebbistatin.…”
Section: Small-molecule Inhibitors Of Myosin Imentioning
confidence: 99%
See 2 more Smart Citations
“…As BDM has turned out to have a broad effect on many other proteins (7) and the inhibitory effect of BTS is limited to fast skeletal muscle myosin, until now blebbistatin has been the only potent tool for specific blocking of myosin II-dependent processes in various species and cell types. Recent data have shown that halogenated pseudilins also have nonspecific inhibitory effects on myosin II isoforms (8)(9)(10).…”
mentioning
confidence: 99%